2013
DOI: 10.2147/cmar.s44539
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of an aprepitant regimen for prevention of chemotherapy-induced nausea and vomiting in patients with breast cancer in the UK

Abstract: PurposePrevention of chemotherapy-induced nausea and vomiting (CINV) remains an important goal for patients receiving chemotherapy. The objective of this study was to define, from the UK payer perspective, the cost-effectiveness of an antiemetic regimen using aprepitant, a selective neurokinin-1 receptor antagonist, for patients receiving chemotherapy for breast cancer.MethodsA decision-analytic model was developed to compare an aprepitant regimen (aprepitant, ondansetron, and dexamethasone) with a standard UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
1
27
1
1
Order By: Relevance
“…This was mainly attributable to the high differential cost between the original granisetron (Kytril ® ) and generic metoclopramide or dexamethasone marketed in Malaysia. Unlike most of the previous pharmacoeconomic studies of antiemetics in chemotherapy which had favored the new treatment (Cox and Hirsch, 1993;Cunningham et al, 1993;Lordick et al, 2007;Lopes et al, 2012;Humphreys et al, 2013), our results had indicated a high ICER (MYR 430.66 per successfully treated patient) of granisetron-based regimen relative to standard regimen. To date, Malaysia does not have a published threshold to determine costeffectiveness of antiemetics.…”
Section: Discussioncontrasting
confidence: 93%
“…This was mainly attributable to the high differential cost between the original granisetron (Kytril ® ) and generic metoclopramide or dexamethasone marketed in Malaysia. Unlike most of the previous pharmacoeconomic studies of antiemetics in chemotherapy which had favored the new treatment (Cox and Hirsch, 1993;Cunningham et al, 1993;Lordick et al, 2007;Lopes et al, 2012;Humphreys et al, 2013), our results had indicated a high ICER (MYR 430.66 per successfully treated patient) of granisetron-based regimen relative to standard regimen. To date, Malaysia does not have a published threshold to determine costeffectiveness of antiemetics.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the cost benefit of aprepitant was not evaluated in those reports. All previous studies that evaluated the cost-effectiveness of aprepitant for CINV in patients receiving chemotherapy, except for HDCT regimens, employed a decision tree model [24][25][26] , and the reasons for the cost benefit were therefore unclear. In our study, cost-effectiveness was analyzed using the direct medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies suggested that aprepitant use with chemotherapy regimens was cost-effective [24][25][26] . However, the economic benefit of aprepitant use has not been elucidated in patients receiving HDCT prior to APBSCT.…”
mentioning
confidence: 99%
“…To date, six studies have compared the cost-effectiveness ratio of antiemetic regimens consisting of aprepitant, a 5-HT3RA, and a corticosteroid with that of a conventional regimen comprising a 5-HT3RA and a corticosteroid for CINV prevention in HEC and in anthracyclines plus cyclophosphamide therapy [7][8][9][11][12][13]. Based on the data from published phase III trials of aprepitant [15,16,[18][19][20], these studies calculated the incremental cost-effectiveness ratio (ICER), which is a ratio of the incremental cost per quality adjusted life years (QALY), as the primary index of cost-effectiveness in a putative setting according to each country's economic status.…”
Section: Cost-effectiveness Of Nk-1 Receptor Antagonistsmentioning
confidence: 99%
“…The cost-effectiveness analyses of NK-1RAs reported to date are all from the perspective of the payer or healthcare system, and outcomes were measured using CINV-related health status (i.e., rates of CP, CR, and IR) [7][8][9][11][12][13]. Regarding medical costs of CINV, all of these reports included only direct medical costs of CINV, and did not analyze indirect costs.…”
Section: From the Patients' Perspectivementioning
confidence: 99%